Host DNases prevent vascular occlusion by neutrophil extracellular traps - Jimenez-Alcazar, Miguel; Rangaswamy, Chandini; Panda, Rachita; Bitterling, Josephine; Simsek, Yashin J.; Long, Andy T.; Bilyy, Rostyslav; Krenn, Veit; Renne, Christoph; Renne, Thomas; Kluge, Stefan; Panzer, Ulf; et al. (Science, 2017)
Platelet and fibrin clots occlude blood vessels in hemostasis and thrombosis. Here we report a noncanonical mechanism for vascular occlusion based on neutrophil extracellular traps (NETs), DNA fibers released by neutrophils during inflammation. We investigated which host factors control NETs in vivo and found that two deoxyribonucleases (DNases), DNase1 and DNase1-like 3, degraded NETs in circulation during sterile neutrophilia and septicemia. In the absence of both DNases, intravascular NETs formed clots that obstructed blood vessels and caused organ damage. Vascular occlusions in patients with severe bacterial infections were associated with a defect to degrade NETs ex vivo and the formation of intravascular NET clots. DNase1 and DNase1-like 3 are independently expressed and thus provide dual host protection against deleterious effects of intravascular NETs.
EVALuna2:13518